2018
DOI: 10.1590/1982-0194201800074
|View full text |Cite
|
Sign up to set email alerts
|

Cateter urinário: o tempo de exposição e calibre podem influenciar na formação de biofilme?

Abstract: 535 30 YEARS 30 YEARS 1 9 8 8 -2 0 1 8 Acta Paul Enferm. 2018; 31(5):535-41.Urinary catheter: can exposure time and gauge affect biofi lm formation?Cateter urinário: o tempo de exposição e calibre podem infl uenciar na formação de biofi lme? Catéter urinario: ¿el tiempo de exposición y calibre puede infl uir en la formación de biofi lm? AbstractObjective: To assess the effects of expos ure time and gauge of Foley catheters in biofi lm formation. Method: In vitro study with samples of Foley catheter fragments m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As for CFUs, it was found that the approval rate in Stage 1 was only 12.5% for the toilet flush handle surface; in Stage 3 that same surface had a 25% approval. Most bacterial populations, regardless of context (environmental, food or medical), tend to form clusters of diverse species constituting a community of microorganisms, i.e., plaques [23,24]. Thus, we cannot overlook the fact that the microbial load on surfaces can be reduced by routine cleaning of the environment, mitigating the contamination [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…As for CFUs, it was found that the approval rate in Stage 1 was only 12.5% for the toilet flush handle surface; in Stage 3 that same surface had a 25% approval. Most bacterial populations, regardless of context (environmental, food or medical), tend to form clusters of diverse species constituting a community of microorganisms, i.e., plaques [23,24]. Thus, we cannot overlook the fact that the microbial load on surfaces can be reduced by routine cleaning of the environment, mitigating the contamination [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The use of medical devices such as urinary catheters are associated with CAUTI (Anjos et al 2020), often linked to the female gender, due to the anatomical characteristics that facilitate the ascension of microorganisms and the colonization of the vagina by members of the fecal microbiota (Conover et al 2019;Malinovski & Estorillo 2021), with the duration of catheterization being a determining risk factor for infection (Kranz et al 2020;Batista et al 2018).…”
Section: Urinary Catheters and Associated Infectionsmentioning
confidence: 99%
“…The presence of biofilm in invasive devices, such as urinary catheters, is still an unmanaged threat. We highlight the importance of structural and organizational biofilm research in order to understand the most intrinsic cellular and molecular characteristics during its development (BATISTA et al, 2018;SANTOS-JUNIOR et al, 2018).…”
Section: Introductionmentioning
confidence: 99%